The Many Difficulties and Subtleties in the Cognitive Assessment of Chronic Hepatitis C Infection - Jefferson Abrantes; Daniel Simplicio Torres; Carlos Eduardo Brandão – Mello (International Journal of Hepatology)
Since the discovery of HCV in 1989, several diseases have been related to chronic infection by this virus. Often, patients with hepatitis C virus (HCV) complain of cognitive impairment even before the development of hepatic cirrhosis, which they described as “brain fog.” Several studies have proposed a link between chronic HCV infection and the development of cognitive alterations, but the inclusion of confounding factors in their samples significantly limits the analysis of the results. In this article, we will give an overview about cognitive dysfunction in patients with HCV.